A Scenario-Planning Framework to Consider the Long-Term Future of the Global Pharmaceutical Industry - Gupta, Shrey; Howard, Megan; Tajudeen, Yusuf Jamal (2014)
This paper uses scenario-planning methodology to consider the long-term future of the global pharmaceutical industry. This is for the year 2034.